Learner Motivation Can It Be Increased by the "Free-Homework" Pass - Glasgow, Melanie C. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
This paper describes the effect of a tangible reward system that was used as a motivator for 92 average-ability suburban junior high school students in an earth science class. Every 2 weeks a student's cumulative performance on daily classroom work and homework was monitored. Each student who completed 100 percent of the work assigned over the 2 weeks was given a "free-homework" pass. The pass could be used in replacement of a future homework assignment for a grade of 100. For a student to receive credit for completing an assignment, a grade of 70 percent or above for the task was required. The pass was a certificate publicly presented to the applause of the other students in the class. Data were collected for a period of 12 weeks, 6 weeks for the pre-treatment and 6 weeks for the treatment period. An analysis of data collected during the treatment indicated that the recognition reward was effective. (JD)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Homework; Junior High School Students; Junior High Schools; Learning Strategies; Rewards; Student Motivation; Reports, Research